PREFERENSI PETANI TERHADAP PENGGUNAAN BENIH PADI DI DESA KOTANEGARA KECAMATAN MADANG SUKU II KABUPATEN OGAN KOMERING ULU TIMUR - Sartika, Eka; Sidik, Muhamad (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2024)
ABSTRACTThis research aims to determine productivity factors, selling prices and quality of rice products to influence rice farmers' preferences for the use of rice seeds. The research results showed that farmers' preferences for the use of rice seeds in Kotanegara Village, Madang Suku II District, East Ogan Komering Ulu Regency, from the three indicators of productivity, selling price and quality of rice, the productivity indicator obtained high results from other aspects where the characteristics of these aspects were able to maintain/ increased production in the last 3 planting seasons and was able to produce production above the village average. The productivity indicators for the four rice varieties are MR at 81%, Ciherang 60%, Ciliwung 55% and Inpari 64%. The productivity indicator is the preferred indicator that is most preferred by farmers in Kotanegara Village, Madang Suku II District, East Ogan Komering Ulu Regency. Farmers' decisions regarding the use of rice seeds in Kotanegara Village, Madang Suku II District, East Ogan Komering Ulu Regency, on five indicators, namely; price, pest and disease resistance, convenience, plant life, shelf life. Farmers' decisions regarding the use of rice seeds with the highest percentage are MR rice seed varieties where, in terms of indicators, price is 82%, pest and disease resistance is 77%, convenience is 82%, plant life is 85%, shelf life is 79%.  ABSTRAKPenelitian ini bertujuan untuk mengetahui faktor produktifitas, harga jual dan kualitas hasil beras untuk mempengaruhi Preferensi petani padi terhadap penggunaan benih padi. Hasil Penelitian didapati preferensi petani terhadap penggunaan benih padi di Desa Kotanegara Kecamatan Madang Suku II Kabupaten Ogan Komering Ulu Timur, dari ketiga indikator produktivitas, harga jual dan kualitas hasil beras, indikator produktivitas mendapatkan hasil yang tinggi dari aspek lainnya dimana karakteristik aspek tersebut mampu mempertahankan/meningkatkan produksi 3 musim tanam terakhir dan mampu menghasilkan produksi diatas rata-rata desa. Indikator produktivitas dari empat varietas jenis padi yaitu, MR sebesar 81%, ciherang 60%, ciliwung 55% dan inpari 64%. Indikator produktivitas menjadi indikator preferensi yang paling banyak disukai petani di Desa Kotanegara Kecamatan Madang Suku II Kabupaten Ogan Komering Ulu  Timur. Keputusan petani terhadap penggunaan benih padi di Desa Kotanegara Kecamatan Madang Suku II Kabupaten Ogan Komering Ulu Timur, pada lima indikator yaitu; harga, ketahanan hama dan penyakit, kemudahan, umur tanaman, daya simpan. Keputusan petani terhadap penggunaan benih padi dengan persetase tertinggi pada varietas benih padi MR dimana, pada indikator, harga 82%, ketahanan hama dan penyakit 77%, kemudahan 82%, umur tanaman 85%, daya simpan 79%.